Development of Integrated Portable Device and Mobile Apps for Homecare System: Body Temperature and Respiration Rate - Edgina Honesta; Agung W. Setiawan (Universitas Ahmad Dahlan, 2021)
A Homecare system is a system that collects patient’ vital signs and health information. Vital signs abnormalities appear several hours before the patient health quality decrease. Therefore, the home care system can be applied to prevent chronic diseases. It is estimated that 25% of chronic disease patients can be prevented by checking vital signs regularly. In this research, an Android-based portable product development that integrates measurements of body temperature and respiration rate is developed. Body temperature will be detected by an infrared temperature sensor. A thermistor will be used to calculate the respiration rate. A thermistor is a resistor whose resistance is dependent on temperature. The accuracy achieved by body temperature measurement is 84% with ±1.37% precision. The accuracy achieved by the respiration rate measurement is 98% with ±3.98% precision. The two gauges are integrated into the microcomputer with a serial communication channel. And then, the measurement results that have been processed on the microcomputer are sent to Android using Bluetooth. Measurement results can be displayed and saved on the Android application. Product portability parameters are measured by weight, size, durability, and power supply. The power supply for this system uses a power bank where the measuring system can be turned on for 3 hours. This research can be applied to a homecare system that collects patients’ vital signs and health information.